Ivermectin Versus Selamectin and Fipronil as Ectoparasite Treatment in Cats and Dogs: A Literature Review - Hermawan, Intan; Desiandura, Kurnia; Wardhani, Hana Cipka Pramuda (Media Kedokteran Hewan, 2024)
Ectoparasite is commonly found on the skin and can cause dermatological problems. In veterinary practices, ivermectin, selamectin, and fipronil are commonly used to treat ectoparasitosis. This article aims to deeply examines the indications and contraindications of ivermectin, selamectin and fipronil. Ectoparasites are commonly found in cats and dogs and make up a large percentage of cases compared to other diseases. Therefore, it is important to have an understanding of the drugs that are effective against ectoparasites. In the past, ivermectin was a popular antiparasitic drug due to its high efficacy. However, its safety is not directly proportional its efficacy. Ivermectin has adverse effects, as evidenced by numerous case reports of overdose, intoxication, and interference with certain organ functions. In the field of pharmacology, many new drugs have been developed with the expectation of improved efficacy and safety. Two examples of such drugs are selamectin and fipronil. This article allows veterinarians and other readers to compare the safety and efficacy of these drugs before administering them to their patients.